Grammar Voyage with ELC030 / Ainul Hafizah Hisyam - Hisyam, Ainul Hafizah (Academy of Language Studies, 2023)
Let’s venture forth into this Grammar Voyage with ELC030! Through this personal report, I hope to share my progress, discoveries, and the joy of conducting grammar activities with students of ELC030. On Tuesday, June 13, I conducted an asynchronous activity, providing students with two sets of tasks. A Google Drive folder was created for students to submit their scores. The tasks were to be completed within class time, spanning from 2 p.m. to 4 p.m.